Kepemimpinan AFILIATIF Dan Kompetensi Profesional Guru Terhadap Pelaksanaan Program Pusat Keunggulan Sekolah Menengah Kejuruan - Okky Erinaldo; Edi Harapan; Syaiful Eddy (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to determine and describe: (1) the influence of affiliative leadership on the implementation of the vocational high school center of excellence program, (2) the influence of teacher professional competence on the implementation of the high school center of excellence program, (3) the influence of affiliative leadership and teacher professional competence together on the implementation of the vocational high school center of excellence program. This study is a quantitative study with a nex post facto design. This study was conducted at SMKN 2 Kayuagung, Ogan Komering Ilir Regency with a sample of 83 respondents. Data collection techniques used questionnaires, observation, and documentation. The validity test used the Statistic Product and Service Solution (SPSS) version 26 program package and the Excel 2019 application, while the reliability test used an internal reliability test obtained by analyzing data from a trial result with the Croanbach's Alpha formula. The data analysis prerequisite test used the normality test, linearity test, and multicollinearity test. While the data description analysis used multiple linear regression analysis. Hypothesis testing used the T Test (Partial Test). The results of the study indicate that (1) there is a positive and significant influence between Affiliative Leadership on the Implementation of the Center of Excellence Program of Vocational High Schools at SMK Negeri 2 Kayuagung, (2) there is a positive and significant influence between Teacher Professional Competence on the Implementation of the Center of Excellence Program of Vocational High Schools at SMK Negeri 2 Kayuagung, (3) there is a positive and significant influence of Affiliative Leadership and Teacher Professional Competence together on the Implementation of the Center of Excellence Program of Vocational High Schools at SMK Negeri 2 Kayuagung.